2007
DOI: 10.1007/s10863-006-9061-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-mediated ATP depletion by anti-cancer agents of the jasmonate family

Abstract: Jasmonates are plant stress hormones that induce suppression of proliferation and death in cancer cells, while being selectively inactive towards non-transformed cells. Jasmonates can overcome apoptotic blocks and exert cytotoxic effects on drug-resistant cells expressing p53 mutations. Jasmonates induce a rapid depletion of ATP in cancer cells. Indeed, this steep drop occurs when no signs of cell death are detectable yet. Experiments using modulators of ATP synthesis via glycolysis or oxidative phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 43 publications
0
22
0
5
Order By: Relevance
“…It therefore appears that it is more specifically the generation of MSO rather than overall ROS that triggers differentiation and apoptosis. Previously, the Flescher lab has shown that jasmonates directly target mitochondria (29,45,46). It therefore remains to be determined whether the MSO generation reported here is a direct effect of MeJ or is an epiphenomenon of mitochondrial damage.…”
Section: Discussionmentioning
confidence: 84%
“…It therefore appears that it is more specifically the generation of MSO rather than overall ROS that triggers differentiation and apoptosis. Previously, the Flescher lab has shown that jasmonates directly target mitochondria (29,45,46). It therefore remains to be determined whether the MSO generation reported here is a direct effect of MeJ or is an epiphenomenon of mitochondrial damage.…”
Section: Discussionmentioning
confidence: 84%
“…We describe here the first jasmonate-binding protein, mammalian hexokinase. Jasmonates are a developing class of anticancer agents (Flescher, 2005(Flescher, , 2007Goldin et al, 2007). In addition, jasmonates are important plant signal molecules (Chini et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These include a higher mitochondrial membrane potential, modulation of the expression of PTPC components and enhanced rates of ATP generation through glycolysis rather than through oxidative phosphorylation (a phenomenon known as the Warburg effect) in cancer cells (Warburg et al, 1930;Pedersen, 1978Pedersen, , 2007aDang and Semenza, 1999;Cuezva et al, 2002;Debatin et al, 2002;Pedersen et al, 2002;Kroemer, 2003Kroemer, , 2006Isidoro et al, 2004;Hay, 2005, 2006;Galuzzi et al, 2006;Mathupala et al, 2006), possibly explaining the selective action of jasmonates on such cells. Indeed, we have found that jasmonates cause significant decreases in cellular ATP levels in cancer, but not in normal cells Goldin et al, 2007;Heyfets and Flescher, 2007). Moreover, positive correlation between the susceptibility of a given cell type to the cytotoxic effect of MJ and the degree of ATP depletion induced in that cell was shown (Goldin et al, 2007).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is important to mention that these mechanisms synergise, but are not necessarily interdependent. On the other hand, the mitochondria proved to be the main target to MeJa induced cell death (Rotem et al, 2005;Goldin et al, 2007). Nonetheless, despite HUVECs and B16F10 melanoma cells presenting similar susceptibility to the toxic milimolar doses of MeJa, as both cell types were unaffected by lower MeJa doses (Figure 2), VEGF production showed a discrete 20% increase at 4 hours exposition (Table 1) and this probably represents an early and transient survival signal.…”
Section: Discussionmentioning
confidence: 97%